Efektivitas Penyampaian Akad-akad BMT NU Blora terhadap Masyarakat Desa - Yusrol Hana; Ulil Azmy; Purnama Wulandari (https://journal.metanusantara.com/impact/index.php/jpk, 2025)
This study aims to measure the extent to which the Tanggel Village community understands the contracts delivered by BMT NU Blora, as well as evaluate the effect of the delivery of contracts on community participation and level of trust in the institution. Clear and transparent contract delivery is expected to increase community understanding of BMT NU Blora's products and services. This research uses a qualitative method with a Participatory Action Research (PAR) approach, which involves the community actively in the research process. The main data sources were Tanggel villagers who are members or recipients of BMT NU Blora services, as well as BMT managers. Data was collected through in-depth interviews, focus group discussions (FGDs), and direct observation of BMT activities. The results show that although the majority of the community understands the basic concepts of the contracts applied, in-depth understanding of the sharia aspects and legal implications is still limited. Factors that influence this level of understanding include the level of education, access to information, and the involvement of religious leaders. Community participation in BMT services is quite high, but the level of trust in the institution is still low, especially related to transparency and clarity of contracts. This study suggests the need to improve two-way communication and educational programmes to strengthen people's understanding and trust in BMT NU Blora.